An assessment of dead wood habitat management and ancient oak conservation in Sherwood Forest National Nature Reserve - Wilcox, Tyler (2016)
The following report is a historical overview and an assessment of dead wood habitat management & ancient oak conservation in Sherwood Forest National Nature Reserve. The following survey report provides the first dead wood survey and results completed for Sherwood Forest NNR, along with a detailed assessment of ancient oak response to the conservation practice of haloing. Line-transect sampling was used in order to predict total volume m3/ha for four study areas and then combined to provide a total overall estimate for Sherwood Forest NNR. Four study areas were chosen in which ten 50 metre transect lines were randomly chosen. The study areas were chosen based on past and present management practices of grazing, non-grazing, and the introduction of oak plantations. A total average volume 211.17 m3/ha of dead wood for logs, snags, and stumps were estimated from the four study areas within Sherwood Forest NNR. There were significant differences between grazed and non-grazed study areas for ancient oak and oak volumes. Significant difference was also found between study area 4 when compared to study areas 1, 2, and 3 for ancient oak dead wood volumes. Study areas 2 and 4 for oak dead wood volume also showed significant difference. These differences can be explained by the past and present management practices within the Park. Of the 211.17 m3/ha of estimated dead wood, 66% (139.96 m3/ha) of total dead wood came from snags and stumps. This was an expected find with the abundance of ancient oak snags and stumps throughout the forest. Compared to previous dead wood surveys performed throughout the UK and Europe Sherwood Forest NNR contains a substantial amount of deadwood habitat. Results of total volume, rot class, and species volume for each individual study area have been displayed within the appendices upon the Sherwood Forest site manager’s request. A total of twenty-six ancient oaks were surveyed separately using information from previous surveys performed in 2005 and 2011. Assessments were made for each oak found alive to determine whether there was any obvious positive or negative response to haloing practices since 2005 using assessment recommendation keys provided within the 2011 survey. Of the twenty-six ancient oaks surveyed sixteen showed positive response, three moderate, six no response at all, and one found dead since the 2010 survey. Epicormic buds, leaf appearance, and overall tree structure provided the basis of comparison from previous surveys to determine the trees response to the haloing method. Overall Sherwood Forest NNR shows very high levels of deadwood based on line-intersect estimates for an old growth forest. Even though the line-intersect method is known to overestimate snag volume and stump volume; with a total of 71.21 m3/ha for just log volume, Sherwood Forest NNR is within the higher third of previous studies.